Supervision Based On Performance In SD Harapan II Binjai - Novianti, Winda (International Journal of Cultural and Social Science, 2022)
The performance or performance of personnel demonstrates dependable human resources. Personnel performance is a description of personnel work that is demonstrated in activities and behavior that refers to the desired process and product as well as the workplace situation. The principal's performance-based supervision is a supervisory activity carried out by superiors to increase the competence of educational staff based on their performance or to increase the effectiveness of the institution in achieving the goals set. Thus, educational human resources who perform at or above the standard set by the institution have the opportunity and the right to receive a response from the institution in accordance with the applicable provisions. This study employs qualitative research methods, with informants including principals, educators, and education staff. The study's findings suggest that an effective supervisory process can improve teacher performance while also achieving organizational goals or the success of school activities. A leader's success will be realized if he treats others or his subordinates well and provides motivation so that they perform well in carrying out their duties. Leadership is the ability to move, motivate, and influence people to take actions aimed at achieving goals by having the courage to make decisions about tasks that must be completed. The principal's supervision of the performance of educators and education staff will be successful if the principal pays attention to the results achieved and treats educators and educators well, allowing them to perform better.